Increased frequency of visits improves the efficiency of surgical global health initiatives - Byaruhanga, Richard; Rourke, Ryan; Awubwa, Michael; Westerberg, Brian D; Rolland, J T; Vaccani, Jean-Philippe (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background The Uganda Hearing Project is a non-profit program assisting with teaching of ear surgery in Uganda. The project started with cadaveric temporal bone courses in 2003 and 2005, including donation of operating microscopes and ear instruments. In 2006, three surgical groups started regular surgical teaching visits. Methods A retrospective chart review of all cases of middle ear surgery performed in Uganda from 2003 to 2009. Surgeries by local surgeons without foreign presence were coded as ‘local’ and those performed with assistance of visiting surgeons were coded as ‘visitors’. Results In 2005, two middle ear surgeries using the operating microscope were done in the Ugandan teaching hospitals by Ugandan Otolaryngologists alone. From the onset of surgical visits in 2006, a total of 193 middle ear surgeries were performed - 115 tympanomastoidectomies, 77 tympanoplasties, and 1 cochlear implant. In 2006 (one surgical teaching visit), 6 middle ear surgeries were performed with visiting surgeon presence and 2 surgeries were performed by the local team alone. This increased in 2007 (2 visits) and again in 2008 (3 visits) to 34 cases with visiting surgeon presence and 48 local cases. Conclusions The temporal bone courses and donation of operating microscopes to Ugandan hospitals have revolutionized middle ear surgery in Uganda. The surgical visits by the Uganda Hearing Project have led to a 24-fold increase in annual middle ear surgeries performed with the operating microscope by Ugandan Otolaryngologists. Increased frequency of surgical visits was correlated with an increase in local surgical output, hopefully resulting in improved care for Ugandans with ear disorders.